Q: Simplify 4p plus 9 plus -7p plus 2?

Write your answer...

Submit

Related questions

4p + 9 - 7p + 2 4p - 7p + 9 + 2 p(4 - 7) + 9 + 2 -3p + 11

Collect like terms together: 4p + 9 + 7p + 2 = (4p + 7p) + (9 + 2) = (4 + 7)p + 11 = 11p + 11 = 11(p + 1)

11p+11

It is: 11p+11 simplified

4p+9-7p+2 -3p+11 p = 11/3

If you mean: 7p-3p+4-2 = 2p-1+10 => 4p+2 = 2p+9 => 2p = 7 Therefore: p = 7/2 => p = 3.5

11-3p

7p + 2 = 5p + 8 7p - 5p = 8 - 2 2p = 6 p = 3

In order to solve for p, you need to get it alone on one side of the equation4p + 7 = 94p = 2 subtract 7 from both sidesp = 2/4 divide by 4 on each sidep= 1/2 simplify

23

5p x 2p = 10p, then 10p / 4p = 2 remainder 2

4p+2 = 3p-7 4p-3p = -7-2 p = -9

7p+2 is an algebraic expression. Since it is neither an equation nor an equality, it cannot have a solution or answer.

-2n - 4p + 2. Without knowing n and p, that's the best you get.

p = -1

8p+2=4p-10 8p-4p=-2-10 4p=-12 p=-12/4 =-3

answer is p/5. problem: {[(p^2)-3p]/[(p^2)-6p+9]}/{20/(4p-12)}

If 3p-5=9-4pthen 3p+4p=9+5=14then 7p=14and p=14/7so p=2Proof:(3 x 2)-5=19-(4 x 2)=1

Points: (p, q) and (7p, 3q) Midpoint: (4p, 2q) Slope: q/3p Perpendicular slope: -3p/q Perpendicular bisector equation:- => y-2q = -3p/q(x-4p) => qy-2q^2 = -3p(x-4p) => qy-2q^2 = -3px+12p^2 => qy = -3px+12p^2+2q^2 In its general form: 3px+qy-12p^2-2q^2 = 0

2(2p + 5q)

4p + 6 = 2 4p = -4 (subtracting 6 from both sides) p = -1 (dividing both sides by 4)

it is -7p + 32: exactly as in the question!

4(7p + 3q - 2)

-8

X= -2